2019
DOI: 10.1016/j.redox.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Dihomo-γ-linolenic acid inhibits growth of xenograft tumors in mice bearing human pancreatic cancer cells (BxPC-3) transfected with delta-5-desaturase shRNA

Abstract: We recently reported that siRNA-knockdown of delta-5-desaturase (D5D), the rate-limiting enzyme converting upstream ω − 6 dihomo-γ-linolenic acid (DGLA) to arachidonic acid, promoted formation of the anti-cancer byproduct 8-hydroxyoctanoic acid (8-HOA) from COX-2-catalyzed DGLA peroxidation, consequently suppressing pancreatic cancer cell growth, migration and invasion. In this study, we have further investigated the anti-tumor effects of D5D-knockdown and the resulting intensified COX-2-catalyzed DGLA peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Expression of p53, procaspase 9, γH2AX and acetyl histone 3 in HCA-7/C29 and its delta-5-desaturase- KD analog upon different treatments in vitro were assessed by western blot as described elsewhere [2430]. For their expressions in vivo , proteins from tumor tissues (~ 50–100 mg) were extracted followed by standard western blot procedures [2430].…”
Section: Methodsmentioning
confidence: 99%
“…Expression of p53, procaspase 9, γH2AX and acetyl histone 3 in HCA-7/C29 and its delta-5-desaturase- KD analog upon different treatments in vitro were assessed by western blot as described elsewhere [2430]. For their expressions in vivo , proteins from tumor tissues (~ 50–100 mg) were extracted followed by standard western blot procedures [2430].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the achievements in surgical resection and chemotherapy for the treatment of gastric cancer, its recurrence rate and metastasis rate are still high, and the median overall survival (OS) time of patients with metastatic disease is still very poor [3,4]. GLA is a promising bioactive molecule that has anticancer ac-tivity in many types of cancer [18,22,26,27], but its biological activity in gastric cancer is poorly understood. It has been reported that regular intake of GLA could reduce inflammation and inhibit the development of cancer [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of DGLA, AA, and PGE2 in A549 cells or tumor tissues were determined by LC/MS as described in the previous studies. 6 , 15 , 47 , 50 For the in vitro test, 3.0 × 10 5 A549 cells were seeded into each well of six-well plates, followed with D5D siRNA transfection or treatment of nanoparticle. For siRNA transfection, A549 cells were randomly assigned to six groups with different treatments with 100 μM DGLA for 12, 24, and 48 h. For nanoparticle treatment, A549 cells were randomly assigned to four groups with different treatments (for 48 h), including control group (treated with the 3WJ-EpCAM nanoparticle, 100 nM), DGLA group (100 μM), 3WJ-EpCAM-D5D siRNA nanoparticle group (100 nM), and DGLA + 3WJ-EpCAM-D5D siRNA nanoparticle group.…”
Section: Methodsmentioning
confidence: 99%
“…The residual was reconstituted in dichloromethane (100 μL) and analyzed by GC-MS as described in the previous studies. 6 , 15 , 47 , 50 The contents of 8-HOA were determined by using the internal standard curve of hexanoic acid (comparing the peak area with the internal standard). For in vivo study, the collected tumor tissues were crushed in a mortar after freezing in the liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation